Robot-Assisted Mckeown Esophagectomy is Feasible After Neoadjuvant Chemoradiation. Our Initial Experience - Goel, Ashish (Indian J Surg, 2016)
Neoadjuvant chemoradiation has become the standard of care for esophageal cancer, especially for middle third esophageal lesions and those with squamous histology. Although more and more thoracic surgeons and surgical oncologists have now shifted to video-assisted and robot-assisted thoracoscopic esophagectomy; there is still limited experience for the use of minimal-assisted approaches in patients undergoing surgery after neoadjuvant chemoradiation. Most surgeons have concerns of feasibility, safety, and oncological outcomes as well as issues related to difficult learning curve in adopting robotic esophagectomy in patients after chemoradiation. We present our initial experience of Robot-Assisted Mckeown Esophagectomy in 27 patients after neoadjuvant chemoradiation, from May 2013 to October 2014. All patients underwent neoadjuvant chemoradiation to a dose of 50.4 Gy/25Fr with concurrent weekly cisplatin, followed by reassessment with clinical examination and repeat FDG PET/CT 6 weeks after completion of chemoradiation. Patients with progressive disease underwent palliative chemotherapy while patients with either partial or significant response to chemoradiation underwent Robot-Assisted Mckeown Esophagectomy with esophageal replacement by gastric conduit and esophagogastric anastomosis in the left neck. Out of 27 patients, 92.5 % patients had stage cT3/T4 tumours and node-positive disease in 48.1 % on imaging. Most patients were middle thoracic esophageal cancers (23/27), with squamous histology in all except for one. All patients received neoadjuvant chemoradiation and subsequently underwent Robot Assisted Mckeown Esophagectomy. The average time for robot docking, thoracic mobilization and total surgical procedure was 13.2, 108.4 and 342.7 min, respectively. The procedure was well tolerated by all patients with only one case of peri-operative mortality. Average ICU stay was 6.35 days (range 3–9 days). R0 resection rate of 96.3 % and average lymph node yield of 18 could be achieved. Pathological node negativity rate (pN0) and complete response (pCR) were 66.6 and 44.4 %, respectively. In the initial cases, four patients had to be converted to open due technical reasons or intraoperative complications. The present study, with shorter operative times, similar ICU stay, overall low morbidity, and mortality and optimal oncological outcomes suggest that robot-assisted thoracic mobilization of esophagus in patients with prior chemoradiation is feasible and safe with acceptable oncological outcomes. It has a shorter learning curve and hence allows for a transthoracic minimally invasive transthoracic esophagectomy to more and more patients, otherwise unfit for conventional approach.